Using classroom asessment to guide instruction - Checkley, John; Bloom, Gary; Steinhorn, Pauline; Association for Supervision and Curriculum Development (Alexandria, VA : ASCD, 2002)
Workshop participants will watch as teachers on these videos use questioning and observation during a lesson, exit cards at the end of class, graphic organizers, peer review, one-on-one conferencing, self-reflection, and student-designed rubrics, to assess their students' understanding
tape 1. Techniques for classroom assessment (30 min.) -- tape 2. The assessment-instruction link (30 min.) -- tape 3. The role of classroom assessment in school improvement (30 min.)
Title from title screen
Editor, bill Creed ; director of photography, Rick Diamond
Keywords: Educational evaluation; Academic achievement -- Testing; Educational tests and measurements